A study on clinical profile and etiological agents of empyema in hospitalised children in Jaipur, India - Meena, Poonam; Jain, Pankaj Kumar; Sharma, Abhishek; Sharma, B. S. (International Journal of Contemporary Pediatrics, 2019)
Background: Objective is to study the clinical profile and etiological agents of empyema in hospitalised children in Jaipur. Methods: This hospital based prospective study was carried out in the Department of Pediatrics, SMS Medical College, Jaipur between April 2016 to March 2017. Children between 1 month to 18 year of age having empyema thoracis (pleural tap showing pus cells under microscopy or on gross examination purulent exudates) were included in the study. Children with Empyema secondary to post-surgical or post-traumatic cause and with tubercular effusion were excluded from the study. Relevant history, clinical examination and investigation were done. Pleural fluid studies were done for cytology, biochemical analysis , culture and antibiotic sensitivity pattern. Results: Total 100 patients were included in study. Out of total 100 patients 62 (62%) were between 1 month to 5 years. Most common symptoms were fever (94%), breathlessness (87%) and cough (85%). 27% patients were severely malnourished as per IAP classification of PEM. Pleural fluid culture was positive in 29 (29%) patients. Most common organism isolated was Staphylococcus aureus (27%), 87.5% isolates of Staphylococcus aureus had sensitivity to vancomycin and linezolid. Conclusions: Empyema thoracis is frequently encountered complication of bacterial pneumonia. Fever, cough, and respiratory distress were the most common presenting complaints and severe acute malnutrition was an important risk factor. Staphylococcus aureus was found to be the most common organism for childhood empyema.